KIRISHMA ATOMLARINI KREMNIYGA ELEKTR MAYDON YORDAMIDA DIFFUZIYA QILISH - Iliyev, X.M.; Isamov, S.B.; Xudoynazarov, Z.B.; O‘.Xolmonov, R.; Isakov, B.O. (SCIENCE and SOCIETY, 2023)
By forming clusters of alloying nickel atoms in silicon by electrodiffusion, a high concentration of alloying atoms was observed in the sample located at the negative pole. It is shown that by controlling the electric field passing through the silicon sample, it is possible to control the concentration of nickel clusters.